Biological activity of probable/possible high‐risk human papillomavirus types in cervical cancer. Issue 1 (9th July 2012) - Halec, Gordana; Schmitt, Markus; Dondog, Bolormaa; Sharkhuu, Enkhtuya; Wentzensen, Nicolas; Gheit, Tarik; Tommasino, Massimo; Kommoss, Friedrich; Bosch, Franz X.; Franceschi, Silvia; Clifford, Gary; Gissmann, Lutz; et al.
Abstract Judging the carcinogenicity of human papillomavirus (HPV) types rarely found in cervical cancer (CxCa) is hindered by lack of studies of their biological activity in cancer tissues. To asses transcriptional activity of HPV types, we have developed ultra‐short amplimer, splice‐site specific, E6*I mRNA RT‐PCR assays for 12 high‐risk (HR)‐HPV (IARC Group 1) and eight probable/possible high‐risk (pHR)‐HPV types (IARC Group 2A/B carcinogens). Previously unreported E6*I splice sites of the six pHR‐HPV types 26, 53, 67, 70, 73 and 82 were identified by cloning and sequencing. We analyzed 97 formalin‐fixed paraffin‐embedded (FFPE) Mongolian CxCa biopsies for presence of HPV DNA by two sensitive genotyping assays, for E6*I transcripts of all HR‐/pHR‐HPV types identified and for expression of HPV surrogate markers p16INK4a, pRb and p53. E6*I of at least one HR‐/pHR‐HPV was expressed in 94 (98%) of cancer tissues including seven with pHR‐HPV types 26, 66, 70 or 82 as single transcribed types. Fifty‐eight of E6*I mRNA transcribing cases were analyzable by immunohistochemistry and displayed p16INK4a overexpression in 57 (98%), pRb downregulation in 56 (97%) and p53 downregulation in 36 (62%) tissues. The newly developed E6*I mRNA RT‐PCR assays appeared to be highly sensitive method to analyze HPV transcription in FFPE materials. Our finding of viral oncogene transcription of pHR‐HPV types 26, 66, 70 and 82 in cervical tumors, in the absence of any other transcriptionally active HR‐type and with p16INK4a overexpression and pRb downregulation, may support a reassessment of the carcinogenicity classification of these pHR‐HPV types.